ĐA DẠNG ĐỊA HỌC VÙNG HÀ TIÊN - KIÊN LƯƠNG - Hải, Hà Quang (Vietnam Journal of Earth Sciences, 2011)
Geodiversity in HaTien - KienLuong Geodiversity may be defined as the range or diversity of geological (rocks, minerals, fossils), geomorphological (landforms and processes) and soil features, including their assemblages, properties, interpretations and systems. The HaTien - KienLuong area contains some of the most important and diversed geological and geomorphological features. There exists the oldest sedimentary formation in the South of Vietnam, almost all types of rocks, various landforms and mineral resources, particularly for construction materials. Many landscapes here were acknowledged as national beauty spots, for instance, Hon Chong mount, Thach Dong and Da Dung mount. However, we have neither a comprehensive evaluation nor an appropriate conservation and management of geodiversity of this area that leads to degradation and destruction of many geosites by natural impacts and human economic development activities. Therefore, an integrated approach to conserve geodiversity is necessary for sustainable development that ensures the benefit of both present and future generations.